The Vibrio parahaemolyticus Small RNA RyhB Promotes Production of the Siderophore Vibrioferrin by Stabilizing the Polycistronic mRNA - Tanabe, Tomotaka (American Society for Microbiology, 2013)
High-affinity iron acquisition in Vibrio parahaemolyticus is mediated by the cognate siderophore vibrioferrin. We have previously reported that the vibrioferrin biosynthesis operon (pvsOp) is regulated at the transcriptional level by the iron-responsive repressor Fur (T. Tanabe, T. Funahashi, H. Nakao, S. Miyoshi, S. Shinoda, and S. Yamamoto, J. Bacteriol. 185:6938–6949, 2003). In this study, we identified the Fur-regulated small RNA RyhB and the RNA chaperone Hfq protein as additional regulatory proteins of vibrioferrin biosynthesis. We found that vibrioferrin production was greatly impaired in both the ryhB and hfq deletion mutants, and a TargetRNA search (http://snowwhite.wellesley.edu/targetRNA/index2.html) revealed that the 5′-untranslated region of pvsOp mRNA (pvsOp 5′-UTR) contains a potential base-pairing region required for the formation of the RyhB-pvsOp 5′-UTR duplex. An electrophoresis mobility shift assay indicated that RyhB can directly bind to the pvsOp 5′-UTR with the aid of Hfq. Rifampin chase experiments indicated that the half-life of pvsOp mRNA in the ryhB and hfq mutants was approximately 3-fold shorter than that in the parental strain, suggesting that both RyhB and Hfq are engaged in the stabilization of pvsOp mRNA. Chrome azurol S assays followed by electrophoresis mobility shift assays and rifampin chase experiments carried out for mutant strains indicated that base pairing between RyhB and the pvsOp 5′-UTR results in an increase in the stability of pvsOp mRNA, thereby leading to the promotion of vibrioferrin production. It is unprecedented that RyhB confers increased stability on a polycistronic mRNA involved in siderophore biosynthesis as a direct target.